Longitudinal Changes in Cardiac Function Based on Serial Tissue Doppler and Doppler Imaging for Patients With Sickle Cell Anemia. (May 2023) - Giray, Dilek; Unal, Selma; Demetgül, Hasan; Karpuz, Derya; Hallioglu, Olgu
Objective: The aim was to evaluate the long-term changes in systolic and diastolic functions with tissue Doppler imaging in children with sickle cell anemia. Materials and Methods: In this study, myocardial performance index of ventricles and mitral and tricuspid valve E/A ratios were calculated. Wall motion velocities of the interventricular septum, right and left ventricles, and mitral and tricuspid annulus were assessed during the systole (Sm), the early diastole (Em), and the late diastole (Am) with pulsed Doppler echocardiography. Results: These diagnostic parameters were obtained from 38 patients (mean 12.5 ± 3.2 years old) who were reached after a mean 6.7 years in long-term follow-up. Left ventricular and septal end-systolic and end-diastolic diameters, and right and left ventricular myocardial performance index were higher in patients ( P < .05 and P = .001, respectively). The Em, Am, and Sm velocities of the right ventricle and septum were significantly lower in the patients at the baseline measures ( P < .05) and all these velocities decreased significantly in patients over time compared with their baseline values ( P < .05). In addition, it was observed that myocardial performance index values of the right and left ventricles increased significantly over time ( P < .05). Conclusion: This is the first study reflecting the age-related changes in global systolic and diastolic functions in sickle cell anemia by serial imaging.